2016
DOI: 10.1002/rcm.7472
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography/chemical ionization triple quadrupole mass spectrometry analysis of anabolic steroids: ionization and collision‐induced dissociation behavior

Abstract: AAS have been divided into three groups according to their ionization behavior and into seven groups according to their CID behavior. Correlations between fragmentation and structure were revealed and fragmentation pathways were postulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 23 publications
(38 reference statements)
1
40
0
Order By: Relevance
“…The unit for the water sample was ng/L, and the units for solid samples were ng/g. Some LODs corresponded to the instrumental method and other LODs in the table corresponded to the developed method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unit for the water sample was ng/L, and the units for solid samples were ng/g. Some LODs corresponded to the instrumental method and other LODs in the table corresponded to the developed method.…”
Section: Resultsmentioning
confidence: 99%
“…The advantages of integrating derivatization with GC/MS and LC/MS/MS analysis include improvement of selectivity and separation, enhancement of ionization efficiency, improvement of structural elucidation, and decrease in endogenous interference . The most widely used derivatization reagents in GC/MS analysis of EDCs are N,O ‐bis(trimethylsilyl)trifluoroacetamide (BSTFA), BSTFA with trimethylchlorosilane (TMCS), N ‐methyl‐ N ‐(trimethylsilyl)trifluoroacetamide (MSTFA), pentafluorobenzyl bromide (PFBBr), acetic anhydride (AA), and MSTFA/ethanethiol/NH 4 I . Besides, several derivatization reagents have also been applied in the LC/MS/MS analysis of EDCs, such as dansyl chloride (DNS‐Cl), pyridine‐3‐sulfonyl chloride, and 10‐methylacridone‐2‐sulfonyl chloride (MASC) .…”
mentioning
confidence: 99%
“… Step 1Based upon the most common metabolic pathways of steroids in human, a list of theoretically potential metabolites is generated. Step 2For all these theoretical metabolites, the expected precursor ion ([M + H] + for most compounds; [M + H] + , [M + H − 90] + and [M + H − 180] + for diols without an oxo function) and the expected product ions are theoretically derived. This selection of precursor ions and product ions is based on the correlation between AAS structure and fragmentation behavior, as clarified in detail in a previous publication . Based on these transitions, a SRM GC‐CI‐MS/MS method is set up.…”
Section: Methodsmentioning
confidence: 99%
“…The authors have reported an LC‐MS screening method incorporating a derivatization step with the use of a pyridine‐carboxylate analogue, picolinic acid, for the detection of over 30 anabolic steroids in equine urine . The recent development in fast‐scanning gas‐chromatography‐triple‐quadrupole mass spectrometry (GC‐MS/MS) has provided a better alternative with a significant reduction in chemical noise by means by selective reaction monitoring (SRM) . The use of GC‐MS/MS fills in the gap for doping analysis of anabolic steroids which exhibits low sensitivity by GC‐MS or low ionization efficiency under ESI by LC‐MS.…”
Section: Introductionmentioning
confidence: 99%